The Educational Thought of Haji Abdul Karim Amrullah and Sheikh Ibrahim Musa: A Comparative Study - Ray Silva; Siti Fatimah (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
This study analyzes the distinctions in philosophical orientation within the Islamic educational thinking of two Minangkabau reformist personalities, Haji Abdul Karim Amrullah and Sheikh Ibrahim Musa, who, despite being educated by the same instructor, formulated markedly divergent educational philosophies. This study employs a comparative historical and qualitative methodology to examine the fundamental sources of the two personalities across six dimensions: epistemology, educational objectives, pedagogical approaches, attitudes towards tradition, institutional strategies, and reform techniques. The results show that Haji Abdul Karim Amrullah adopted a pragmatic approach that values information for its social usefulness. He focused on community change, experiential-inductive approaches, and confrontational reform. On the other hand, Sheikh Ibrahim Musa had an idealistic view that information is valid only if it fits with ancient scholarly traditions. He stressed deep intellectual growth, text-based, deductive, systematic techniques, and gradual educational change. This difference shows two distinct approaches to addressing the relationship between religious authenticity and modern relevance in the context of colonialism and early Indonesian nationalism. This research helps dismantle the singular narrative of Islamic modernism and offers a reproducible comparative analytical framework for examining Islamic educational philosophy in other contexts